Causal linkage between angiotensin-converting enzyme 2 and risk of lung cancer: a bidirectional two-sample Mendelian randomization study - Chen, Shubin; Ning, Ruiling; Jiang, Wei; Zhou, Shaozhang; Yu, Qitao; Gan, Haijie (Frontiers in Medicine, 2024)
Background: Observational studies suggest a connection between ACE2 (angiotensin-converting enzyme 2) and lung cancer. However, it's not apparent if confounding variables are interfering with the link. Therefore, we aimed to define the relationships between ACE2 and the risk of lung cancer. Methods: With the aim of developing genetic tools, we selected SNPs substantially associated with ACE2 using a statistically significant criterion. The relevant SNPs were then taken from the lung cancer GWAS dataset for additional research. After that, we used two-sample Mendelian randomization (MR) to ascertain if ACE2 is causally linked to the risk of developing lung cancer. To investigate the causal links' directions, we also performed a reverse MR analysis. Results: According to our findings, there is strong evidence that ACE2 is linked to a decreased chance of developing lung cancer (odds ratio: 0.94; 95% confidence interval: 0.90-0.98; P = 0.0016). The IVW method, the major MR analysis, was not impacted by heterogeneity in any of the analyses, according to Cochrane's Q test (PCochrane' s Q=0.207). The MR-Egger intercept (Pintercept=0.622) showed no indication of horizontal pleiotropy in any of the investigations. Outlier SNPs were not detected by the MR-PRESSO global test (Pglobal test=0.191). The leave-one-out analysis was performed, and the results showed a steady outcome. Nonsignificant causal estimates between lung cancer and ACE2 were produced by reverse MR analysis. Conclusion: MR investigation revealed a significant causal link between ACE2 and the risk of getting lung cancer. These findings may have implications for public health measures aimed at reducing the incidence of lung cancer.